Polychaetes from Santa Catarina State (southern Brazil): checklist and remarks on species distribution - Pagliosa, Paulo Roberto; Doria, João Gabriel; Alves, Giorgia Freitas; de Almeida, Tito Cesar Marques; Lorenzi, Luciano; Netto, Sergio Antonio; Da Cunha Lana, Paulo (Zootaxa, 2012)
This study summarizes taxonomic information on polychaetes from Santa Catarina State, southern Brazil, between25º57'S and 29º23'S, and provides species distribution records together with information on habitats, based on historicaldata and novel records from primary surveys. Rarefaction curves showed that most species were found in the shallowsublittoral (to 60 m) rather than in deep sublittoral (>60 m) or estuarine habitats. Altogether, 228 valid species belongingto 141 genera and 44 families were recorded. This inventory adds 141 new records to previous regional reports. We founda shift in occurrence of species when comparing data from the study area with data from both southward (29–33º S) andnorthward (23–26º S) sites. Few species were shared between consecutive sites: this could be a response to the regionalbehaviour of the atmosphere and water masses, with a progressive increase in the influence of subantarctic waters and a decrease in the influence of subtropical waters.